2015
DOI: 10.1007/s00330-015-3606-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term precision assessment of trabecular bone score and bone mineral density using dual-energy X-ray absorptiometry with different scan modes: an in vivo study

Abstract: • TBS is an emerging tool for assessing BMD. • TBS reproducibility is lower than that of BMD. • Differences between imaging modes are not significant for either TBS or BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Secondly, DXA is able to measure BMD at those sites particularly relevant to osteoporotic fractures, such as lumbar spine and proximal femur, and measurements at these sites are optimal to predict fracture risk (17). The reproducibility of BMD measurements is very good, with a coefficient of variation (CoV) that ranges from 1% at lumbar spine to 2% at femoral neck (14,18,19). Lastly, DXA scans are widely available worldwide with very low scanning time (1-3 minutes).…”
Section: Dxamentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, DXA is able to measure BMD at those sites particularly relevant to osteoporotic fractures, such as lumbar spine and proximal femur, and measurements at these sites are optimal to predict fracture risk (17). The reproducibility of BMD measurements is very good, with a coefficient of variation (CoV) that ranges from 1% at lumbar spine to 2% at femoral neck (14,18,19). Lastly, DXA scans are widely available worldwide with very low scanning time (1-3 minutes).…”
Section: Dxamentioning
confidence: 99%
“…Trabecular bone score (TBS) is a recently implemented tool that provides a grayscale textural analysis of lumbar spine DXA images, showing the potential to be a BMDindependent fracture risk predictor (18,38,39). TBS is able to measures the variations in gray-level texture between adjacent pixels from DXA raw data; ex vivo studies confirmed that TBS was strongly correlate to micro-CT parameters, such as bone volume, tissue volume or trabecular number (40,41).…”
Section: Additional Tools Of Dxamentioning
confidence: 99%
“…24 On the other hand, TBS and BMD precision on iDXA instrument were found comparable, without significant differences between males and females (% coefficient of variation of L1-L4 BMD and TBS, 1.9% and 1.4%, respectively). 10 Accumulating evidence suggests that TBS used in addition to aBMD improves the prediction of osteoporotic fracture risk, 13,15,19,25,26 especially in patients with aBMD in the range of normality or osteopenia.…”
Section: Discussionmentioning
confidence: 88%
“…13 This caution is derived from several limitations pertinent to TBS. These include the current lack of TBS cutoff values for fracture prediction, a reduced short-term intrascan precision of TBS in comparison with BMD, 14 and the presence of notable interscanner differences in TBS values. 15 Additional work on quality control (development of specific TBS phantoms, scanner cross-calibration) and further clinical studies are necessary to determine whether TBS will prove appropriate for routine clinical use.…”
Section: Techniques To Measure Bone Quality Trabecular Bone Scorementioning
confidence: 99%